Painel III - Aliança no e-business e-business alliances (coalitions) - Bessa, Antonio Fernando; Cohen, illian E.; Teixeira, Cleveland Prates; Calliari, Marcelo; Franceschini, José Inácio Gonzaga; Barrionuevo, Arthur; Ariboni, Pietro (Revista do IBRAC, 2025)
Coordenador/Chairman: Dr. Antonio Fernando Bessa .................... 159 Dr. Willian E. Cohen .................... 159 Dr. Cleveland Prates Teixeira .................... 170 Dr. Marcelo Calliari .................... 189 Dr. José Inácio Gonzaga Franceschini .................... 208 Dr. Arthur Barrionuevo .................... 211 Dr. Pietro Ariboni .................... 215 DEBATES .................... 217